A Survey on the Intensity of Lighting in Elementary Schools of Bojnurd City - Faeze SEPAHI ZOERAM; Fateme PAKRAVAN; Morteza ESMAILZADE KAVAKI; Neda VAHIDI (Shahid Sadoughi University of Medical Sciences, 2022)
Background and Aim: Optimal lighting should create a balance between economy and the environment. In order to comply with safety and health principles of the staff, proper lighting of the work environment should be provided for everyday tasks. Inappropriate lighting conditions cause distortion of environmental visual information, and increase the likelihood of mistakes in the work. The quality of lighting is important for creating willingness to study, visual comfort, and productivity in the learning process of students. The subject of this research is the manner and intensity of lighting in schools, in the city of Bojnurd, in elementary education centers. It, also, tries to assess the quality of lighting schools, identify problems in school lighting systems, and provide appropriate solutions for improvement. Materials and Methods: This descriptive study was randomly selected in girl's elementary schools of Bojnourd, during autumn of 1395, in 10 schools in different regions of the city. The overall lighting (natural and artificial) and natural light were measured individually, using the Hanger CE Lux Meter. Collected data, including total brightness, natural, and artificial of classes, were analyzed by SPSS software (version 18). For each class, the minimum, maximum and average brightness and standard deviation were calculated based on the lux. Also, the type of lamps, defective lamps, wall colors and the quality of devices and equipment were studied. Results: Results showed that in 90% of cases, the intensity of lighting was consistent with standard values, and in 10% of cases, the lighting intensity was not in accordance with the standard. In 87.57% of the cases, the type of lamps was suitable for lighting of the school and classes, and in 94.1% of the cases the lamps were burned out and defective. Conclusion: The lack of natural and artificial lighting in schools due to the incorrect placement of windows, inappropriate distribution of lamps, as well as the ratio of the surface to the window, are the causes of inappropriate status of lighting efficiency system.